2021
DOI: 10.3390/catal11111404
|View full text |Cite
|
Sign up to set email alerts
|

Hybrids of Reduced Graphene Oxide Aerogel and CNT for Electrochemical O2 Reduction

Abstract: Carbon nanotubes (CNTs), graphene aerogels (GAs), and their hybrid (CNT-GA) prepared by hydrothermal treatment were tested in the electrocatalytic oxygen reduction reaction (ORR). The importance of porous structure derived from the combination of mesoporosity coming from CNTs with macroporosity stemming from GAs was evidenced because the hybrid carbon material exhibited synergistic performance in terms of kinetic current and onset potential. Different electrocatalysts were prepared based on these hybrids doped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…GO has been shown in the literature that it can be organized into lightweight, porous, 3D structures such as aerogels, foams, or sponges in several ways. However, some structural disadvantages, mainly fragility and mechanical instability, restrict their use in several applications such as supercapacitors, batteries, membranes for water purification or gas separation, and electromagnetic interference shielding [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…GO has been shown in the literature that it can be organized into lightweight, porous, 3D structures such as aerogels, foams, or sponges in several ways. However, some structural disadvantages, mainly fragility and mechanical instability, restrict their use in several applications such as supercapacitors, batteries, membranes for water purification or gas separation, and electromagnetic interference shielding [ 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [16] the authors obtained a composite material suitable for the oxygen electrochemical reduction, and in Ref. [17] the authors reported on producing the adsorbent with magnetic properties.…”
Section: Introductionmentioning
confidence: 99%